PENGEMBANGAN BAHAN AJAR MATA KULIAH ANALISA KOMPLEKS DENGAN MENGGUNAKAN STRATEGI INQUIRY DI STKIP TAPANULI SELATAN - siregar, yulia pratiwi (JURNAL EDUCATION AND DEVELOPMENT, 2018)
The purpose research is how to know about validation, prackticalities, and effectiveness from the complex analysis with make strategy inquiry. Based on the research 4 these are: 1) Define, 2) Design, 3) Develop, and 4) Disseminated. This research done in the test phase is performed on seventh grade B students STKIP Tapanuli Selatan totaling 18 students. The Instrument of research validated by a validator 3 students who have the same background with the research carried. Based on calculation validation obtained a value of 118 with a percentage of 75,6%. So it can be conclude that the analysis of complex materials using the inquiry strategy is valid and can be used for the learning process in the course of complex analysis. Subsequent to the calculation of the practicalities of teaching material obtained a value of 588 with a percentage of 77% so it can be concluded that the complex analysis of teaching materials using the inquiry practical strategies. For use in one of the learning process of teaching materials and reference in learning. The last stage of the calculations in this research is to best the effetiveness of teaching materials and based on the calculation result obtained percentage of 57%. So, it can be conclude that the analysis complex materials using the inquiry strategy effective for use as teaching materials in class because it can enhance activity of the students in learning and can improve cognitive abilities and other mathematical abilities.